The education thrust: Selected addresses - Robinson, Arthur Napoleon Raymond, Prime Minister (Government Printery, 1988)
This publication contains three speeches. The first speech, delivered at the launching of the Local School Boards Pilot Project, Chaguanas Senior Comprehensive School on 19 March, 1988, states that education is important to national development because of its unique power in achieving a local social revolution that will change our future. The second speech, delivered at the inauguration of the Post Primary Pilot Project at Egypt Village Government Post Primary Centre on 11 April, 1988, saw this opening as an effort to channel some of those who fail Common Entrance into new post-primary areas. The third speech was made at the formal opening of the Point-a-Pierre Government Special School on 22 April 1988. This school is one of those meant to provide education for the disabled through government control rather than through voluntary groups as in the past
Keywords: Speeches